The Correlation of Forensic Science Role : Forensic Photography, Forensic Toxicology and Digital Forensics Towards the Evidence in the Criminal Justice System - Nurul Rahma Windyani, Ersa; A. Acbay, Femalie (Dinasti Research, 2023)
The Role of Forensic Photography, Forensic Chemistry Toxicology and Digital Forensic on Pembuktian is a scientific article in the literature review within the scope of the field of Law and Criminology. The purpose of this article is to build a hypothesis of the influence between variables that will be used in further research. Research objects in online libraries, Google Scholar, Mendeley and other academic online media. The research method with the research library comes from e-books and open access e-journals. The results of this article: 1) Fotografi Forensik has an effect on Pembuktian; 2) Toksikologi Forensik has an effect on Pembuktian; and 3) Forensik Digital has an effect toward the Evidence.